Efficiency Marketing Chain Analysis of Sangkuriang Catfish in Minapolitan Area - Abel Gandhy; Venty F Nurunisa; Ternando Situmeang (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2019)
Aquaculture is an alternative of sustainable solution to meet the high demand of fish. One type of fish that is most easily cultivated and preferred by consumers is catfish. West Java Province is the largest producer of catfish, and Bogor is the central area of catfish production in West Java. Parung subdistrict, is one of Minapolitan Area in Bogor which focuses on catfish cultivation. As a Minapolitan Area, it is very important to examine the integration between each institution,examine which institutions involved in the supply chain to gather perfect market information and clear market identification. The objectives of this study are to analyzethe pattern of Sangkuriang catfish trading channel, the function of trading, and the efficiency of the catfish marketing chain. Selection of respondents using purposive sampling, by setting 50 of catfish cultivators as respondents. There are 4 marketing channels in Parung Subdistrict. Institutions involved in the marketing of catfish are cultivators, collecting traders, agents, market traders, Restaurant/Foodstalland end consumers.The second channel (Farmers-Retailers-Restaurant/Food Stall) is the most efficient channel.Shorter marketing chains create higher farmer’s share.